Anticancer Role of PPARγ Agonists in Hematological Malignancies Found in the Vasculature, Marrow, and Eyes. (31st January 2010) - Simpson-Haidaris, P. J.; Pollock, S. J.; Ramon, S.; Guo, N.; Woeller, C. F.; Feldon, S. E.; Phipps, R. P.
Abstract : The use of targeted cancer therapies in combination with conventional chemotherapeutic agents and/or radiation treatment has increased overall survival of cancer patients. However, longer survival is accompanied by increased incidence of comorbidities due, in part, to drug side effects and toxicities. It is well accepted that inflammation and tumorigenesis are linked. Because peroxisome proliferator-activated receptor (PPAR)-γ agonists are potent mediators of anti-inflammatory responses, it was a logical extension to examine the role of PPARγ agonists in the treatment and prevention of cancer. This paper has two objectives: first to highlight the potential uses for PPARγ agonists in anticancer therapy with special emphasis on their role when used as adjuvant or combined therapy in the treatment of hematological malignancies found in the vasculature, marrow, and eyes, and second, to review the potential role PPARγ and/or its ligands may have in modulating cancer-associated angiogenesis and tumor-stromal microenvironment crosstalk in bone marrow.